Pełnik europejski Trollius europaeus L. w zbiorowiskach leśnych i okrajkowych północnej części Niziny Południowopodlaskiej - Ciosek, Marek; Krechowski, Janusz; Piórek, Katarzyna (Leśne Prace Badawcze, 2013)
The distribution of Trollius europaeus in the northern part of the Południowopodlaska Lowland was described and a phytosociological study made of the localities where it was present between 2010 and 2012. The condition of all sites where T. europaeus was historically present was also verified. These field studies reveal that the number of sites of occurrence and the abundance of T. europaeus populations have rapidly diminished over recent years. Only 15 populations of the species in the vicinity of 7 sites were confirmed. Trollius europaeus is usually considered a species characteristic of moist meadows of ordo Molinietalia and in the plant community type, Polygono bistortae-Trollietum . In the northern part of the Południowopodlaska Lowland, no meadow sites containing Trollius europaeus still remain according to our survey. All the confirmed stands are situated in deciduous forests of class Querco-Fagetea ( Tilio-Carpinetum and Potentillo albae-Quercetum ) and moist forest edge communities of ordo Glechometalia. The disappearance of all meadow populations is mainly considered a result of intensification of the agricultural use of these habitats. We suggest that the category of threat to Trollius europaeus is increased on the regional list from VU to EN, and consolidated with further monitoring and active protection of stands where it is present.